Effects of Spartina alterniflora invasion on the communities of methanogens and sulfate-reducing bacteria in estuarine marsh sediments - Zeleke, Jemaneh; Sheng, Qiang; Wang, Jian-Gong; Huang, Ming-Yao; Xia, Fei; Wu, Ji-Hua; Quan, Zhe-Xue (Frontiers in Microbiology, 2013)
The effect of plant invasion on the microorganisms of soil sediments is very important for estuary ecology. The community structures of methanogens and sulfate-reducing bacteria (SRB) as a function of Spartina alterniflora invasion in Phragmites australis-vegetated sediments of the Dongtan wetland in the Yangtze River estuary, China, were investigated using 454 pyrosequencing and quantitative real-time PCR (qPCR) of the methyl coenzyme M reductase A (mcrA) and dissimilatory sulfite-reductase (dsrB) genes. Sediment samples were collected from two replicate locations, and each location included three sampling stands each covered by monocultures of P. australis, S. alterniflora and both plants (transition stands), respectively. qPCR analysis revealed higher copy numbers of mcrA genes in sediments from S. alterniflora stands than P. australis stands (5- and 7.5-fold more in the spring and summer, respectively), which is consistent with the higher methane flux rates measured in the S. alterniflora stands (up to 8.01 ± 5.61 mg m-2 h-1). Similar trends were observed for SRB, and they were up to two orders of magnitude higher than the methanogens. Diversity indices indicated a lower diversity of methanogens in the S. alterniflora stands than the P. australis stands. In contrast, insignificant variations were observed in the diversity of SRB with the invasion. Although Methanomicrobiales and Methanococcales, the hydrogenotrophic methanogens, dominated in the salt marsh, Methanomicrobiales displayed a slight increase with the invasion and growth of S. alterniflora, whereas the later responded differently. Methanosarcina, the metabolically diverse methanogens, did not vary with the invasion of, but Methanosaeta, the exclusive acetate utilizers, appeared to increase with S. alterniflora invasion. In SRB, sequences closely related to the families Desulfobacteraceae and Desulfobulbaceae dominated in the salt marsh, although they displayed minimal changes with the S. alterniflora